Impact of COVID-19 on HIV Preventive Services for Pregnant Women in Kenya: A Comparative Study across Nairobi, Machakos, and Kajiado Counties - Vesonder, Modesta (International Journal of Health Sciences, 2025)
Purpose: This study investigates the impact of the pandemic on access to prenatal and postnatal HIV services for pregnant women living with HIV (WLHIV) in Nairobi (urban), Machakos (semi-urban), and Kajiado (rural/semi-arid) counties in Kenya. Methodology: A retrospective comparative study design was employed to analyze historical healthcare data from 2019 to 2022. Data were collected from government health records and included the number of pregnant WLHIV receiving antiretroviral therapy (ART) before and during the pandemic, the percentage of pregnant WLHIV attending antenatal care (ANC) visits, MTCT rates, and the number of infants born to HIV-positive mothers receiving ART prophylaxis. Descriptive and inferential statistical analyses were conducted using SPSS software to compare HIV service accessibility and MTCT rates across the three counties before and during the pandemic. Findings: The study found that urban counties, such as Nairobi, experienced minimal disruptions, with 85% of pregnant WLHIV continuing to access ART, and MTCT rates remaining stable at 6.5%. In contrast, semi-urban and rural counties, such as Machakos and Kajiado, faced severe service accessibility barriers due to facility closures, reductions in healthcare providers, economic hardships, and pandemic-related mobility restrictions. In Machakos, ART access declined to 65% (from 75%), while MTCT rates increased from 8% to 12%. The situation was even more severe in Kajiado, where only 50% of pregnant WLHIV accessed ART (down from 70%), and MTCT rates surged from 10% to 18%. Unique Contribution to Theory, Practice, and Policy: This study highlights the public health impact of healthcare service disruptions on women living with HIV (WLHIV), emphasizing the need for resilient healthcare systems to sustain essential services during crises. It reveals urban-rural disparities in HIV service access, showing that rural healthcare systems are more vulnerable to external shocks. The study underscores the importance of community-based healthcare models, such as mobile clinics and decentralized ART distribution, to maintain HIV care in emergencies. From a policy perspective, it advocates for telemedicine expansion, mobile clinic deployment, emergency ART stockpiling, and flexible ANC service models to strengthen Kenya’s healthcare system and protect maternal and child health.